Length-weight relationship of a mesopelagic shrimp, Oplophorus typus from the west coast of India - Karuppasamy, P K; Menon, N G (Indian Journal of Fisheries, 2011)
Length-weight relationship of a mesopelagic shrimp, Oplophorus typus from the west coast of India